2011
DOI: 10.1111/j.1469-8986.2010.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

EEG power changes reflect distinct mechanisms during long‐term memory retrieval

Abstract: The roles of theta and alpha oscillations for long-term memory (LTM) retrieval are still under debate. Both are modulated by LTM retrieval demands, but it is unclear what specific LTM functions they are related to. Here, different oscillatory correlates of LTM retrieval could be obtained for theta and alpha with a paradigm that is suited to monitor the activation of a varying number of material-specific LTM representations. Both frequency bands responded parametrically to the number of retrieved items. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 47 publications
10
73
0
Order By: Relevance
“…A number of previous studies have shown that frontal theta power varies as a function of interference in response conflict tasks Cavanagh et al, 2009) and more specifically during episodic memory retrieval (Khader and Rösler, 2011). For instance, higher levels of theta power are obtained during competitive retrieval when compared to noncompetitive memory retrieval .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A number of previous studies have shown that frontal theta power varies as a function of interference in response conflict tasks Cavanagh et al, 2009) and more specifically during episodic memory retrieval (Khader and Rösler, 2011). For instance, higher levels of theta power are obtained during competitive retrieval when compared to noncompetitive memory retrieval .…”
Section: Discussionmentioning
confidence: 98%
“…Decreased alpha power is considered to reflect the higher excitability of cell assemblies in sensory areas, allowing facilitated processing of target information in selective attention and working memory (e.g., Sauseng et al, 2005; Thut et Lundqvist et al, 2011) and indicating material-specific sensory reactivation of long-term memories (Khader and Rösler, 2011). A larger decrease in this frequency range has been observed in high load and interference conditions (Khader and Rösler, 2011;Lundqvist et al, 2011). Parallel effects are evident in our data and presumably indicate the effortful reactivation of neural populations housing sensory features of episodic memories.…”
Section: Discussionmentioning
confidence: 99%
“…The theta activity is also higher during encoding than retrieval, being related more to the access of a stored code than to more general processes (Klimesch et al, 2001). On the other hand, the alpha activity seems functionally related to the activation of stored information, and both the alpha power decrease and the theta power increase are functionally independent (Khader and Rösler, 2010). Our results, in showing that success/ failure of dream recall is related to specific cortical EEG activity and oscillations during the sleep stage preceding awakening, also suggest that the intrinsic differences in the basic electrophysiology of the NREM stage 2 and REM sleep may determine which cortical EEG oscillation (i.e., frontal theta or right temporal alpha) is predictive of dream recall after awakening.…”
Section: Nrem Dream Recallmentioning
confidence: 99%
“…In particular, theta-band (4-8 Hz) activity has often been observed in relation to memory processes (e.g., Jacobs, Hwang, Curran, Kahana, 2006;Khader & Rösler, 2011; see for reviews Düzel, Penny, & Burgess, 2010;Klimesch, 1999;Nyhus & Curran, 2010), also involving the retrieval of lexical-semantic information during language comprehension (e.g., Bastiaansen et al 2005Bastiaansen et al , 2008. Oscillations in the alpha band (8-15…”
Section: Introductionmentioning
confidence: 99%
“…This oscillatory activity is typically categorised into different frequency bands. Different cognitive functions have been associated with frequency-specific changes in oscillatory power (e.g., Engel & Fries, 2010;Hanslmayr, Staudigl, & Fellner, 2012;Jensen & Mazaheri, 2010;Khader & Rösler, 2011;Van Ede, de Lange, Jensen, & Maris, 2011).…”
Section: Introductionmentioning
confidence: 99%